Eau : le rôle méconnu de Michel Rocard - Bernard Barraqué; Patrick Laigneau; Pierre Victoria (Développement Durable et Territoires)
Michel Rocard was not a water specialist, but he repeatedly supported water policy improvements: he protected the water agencies in an Accounting Office audit when he was sent to condemn them; as prime minister he supported the law that made water a common heritage; in the latter part of his life, he was active in the world water forums. What a pity he could not know the work of Elinor Ostrom back in the 1990s.